Determinants of The Level of Information Disclosure in Financial Statements Prepared in Accordance With IFRS - Anna Białek-Jaworska; Anna Matusiewicz (Journal of Accounting and Management Information Systems (JAMIS), 2015)
This paper aims to identify the factors determining the extent of mandatory and voluntary information disclosure in financial reports of selected Polish listed companies. It is particularly important in the context of reporting standards harmonisation and the related process of IFRS coming into common use in consolidated accounts since 2005. We used the Polish Corporate Disclosure Index (PCDI), designed by the research team led by Swiderska (2010), for non-financial companies. The PCDI index includes voluntary disclosures in financial statements, management reports and corporate social responsibility reports. Based on a panel study of factors determining the scope of information disclosed by 36 Polish public parent companies, forming capital groups, in the years 2005-2007 we demonstrated a negative correlation between the extent of mandatory and voluntary disclosure and the companies' financial performance (ROE) except for possitive relation with disclosure in management reports. Probably, managers prefer to show off good results in management reports (impression management theory). When the company profitability was lower, managers explained the financial standing in more detail (signaling theory). Auditor plays the important role in voluntary and corporate social responsibility disclosures, but not in mandatory ones. Bigger companies disclose more in each area, in accordance with agency theory.
Keywords: M41; M42; G32; 650; IFRS; Poland; mandatory disclosure; voluntary disclosure